119k views
0 votes
Find f(g(2)) simplify completely f(x)= 6x+9 g(x)=3x

User Murat Kara
by
4.8k points

2 Answers

3 votes

Answer:

f(g(2)) = 45

Step-by-step explanation:

  • f(x) = 6x + 9
  • g(x) = 3x

Finding g(2)

  • g(2) = 3(2)
  • g(2) = 6

Solving f(g(2))

  • f(g(2))
  • f(6)
  • f(6) = 6(6) + 9
  • f(6) = 36 + 9
  • f(6) = 45
  • f(g(2)) = 45
User Mayur Padshala
by
4.7k points
1 vote

Answer:

45

Step-by-step explanation:

Given:

f(x)= 6x+9

g(x)=3x

Go from right to left in such function questions

⇒ f(g(2))

⇒ f(3(2))

⇒ f(6)

⇒ 6(6) +9

⇒ 36 + 9

⇒ 45

User Egryan
by
5.3k points